Assessment of genetic variation and trait inter-relationship in QPM inbred lines in Vindhyan region of Eastern Uttar Pradesh - Phansal, Ankit; Marker, Shailesh; Aggarwal, Rajesh (Journal of Cereal Research, 2022)
The present investigation was carried out to assess genetic variation and trait inter-relationship in QPM inbred lines in Vindhyan region of Eastern Uttar Pradesh for 18 characters during Rabi 2018-19. Analysis of variance showed significant differences for all the characters at 1 per cent level of significance, indicating that considerable genetic variability was present among different QPM inbred lines. The less difference between GCV and PCV revealed that there was a very low influence of environment on the expression of various characters. High heritability coupled with high genetic advance as per cent mean was depicted by for cob weight with sheath followed by cob weight without sheath and tassel length. Plant height followed by kernels per row, cob height, cob weigh twith sheath, tassel length, cobs per plant, cob weight without sheathand cob length showed positive significant correlation with grain yield and days to 50 per cent silking, followed by kernels per row,biological yield, harvest index, tassel length, cob length, anthesis silkinginterval, cobs per plant and cob weight without sheath hadshown the positive direct effect on grain yield per plant. Therefore, these characters may be used as selection indices for genetic improvement of QPM inbred lines.